2002
DOI: 10.1136/thorax.57.9.759
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bacterial colonisation and the frequency, character, and severity of COPD exacerbations

Abstract: Background: Patients with chronic obstructive pulmonary disease (COPD) are prone to frequent exacerbations which are a significant cause of morbidity and mortality. Stable COPD patients often have lower airway bacterial colonisation which may be an important stimulus to airway inflammation and thereby modulate exacerbation frequency. Methods: Twenty nine patients with COPD (21 men, 16 current smokers) of mean (SD) age 65.9 (7.84) years, forced expiratory volume in 1 second (FEV 1 ) 1.06 (0.41) l, FEV 1 % predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
442
2
26

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(489 citation statements)
references
References 38 publications
19
442
2
26
Order By: Relevance
“…These results broadly concur with Patel et al who reported a positive correlation between lower airway bacterial colonization and exacerbation frequency [22]. In contrast to previous reports that associated tobacco exposition with rates of bacterial colonization [14,22], we observed no difference. Given the requirement for tobacco abstinence prior to lung transplantation evaluation, rates of active smoking in our cohort were extremely low, with elevated Hb-CO being identified in only 4% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…These results broadly concur with Patel et al who reported a positive correlation between lower airway bacterial colonization and exacerbation frequency [22]. In contrast to previous reports that associated tobacco exposition with rates of bacterial colonization [14,22], we observed no difference. Given the requirement for tobacco abstinence prior to lung transplantation evaluation, rates of active smoking in our cohort were extremely low, with elevated Hb-CO being identified in only 4% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Bacterial colonization of the airways in COPD patients with even mild airfl ow obstruction is frequent (Soler et al 1999;Sethi et al 2006), and hence these particular microbes seem to be likely suspects as the source of disease-causing exogenous antigens. These bacterial colonizations are associated with recurrent COPD exacerbations, more rapid declines in lung function, and are correlated with a number of infl ammatory markers in sputum and in BAL Patel et al 2002;Wilkinson et al 2003;Banerjee et al 2004).…”
Section: Microbial Peptide Antigensmentioning
confidence: 99%
“…IL-8 levels are increased in sputum of patients with COPD (Keatings et al 1996;Yamamoto et al 1997), and are further augmented during disease exacerbations, presumably in association with neutrophilic infl ammation triggered by bacteria (Crooks et al 2000;Aaron et al 2001;Gompertz et al 2001). Airway microbes induce IL-8 secretion by epithelial cells, and levels of this cytokine have been shown to correlate with airway bacterial load Patel et al 2002). Interestingly, blocking antibodies to IL-8 only led to a modest reduction in the neutrophilic infl ammation (Beeh et al 2003).…”
Section: Interleukin-8 (Il-8)mentioning
confidence: 99%
“…Among them, interleukin (IL)-8, a member of the CXC chemokine family, plays a pivotal role in regulating neutrophil and monocyte chemotaxis toward sites of infection, and in inducing airway inflammation [9,10]. The presence of microorganisms such as M. catarrhalis in the lower respiratory tract of COPD patients has been found to increase IL-8 release in bronchoalveolar lavage of COPD patients, which is associated with disease progression [11][12][13]. Transcriptional regulation of IL-8 is controlled by a tight regulatory signalling network, most importantly involving the nuclear factor (NF)-kB.…”
mentioning
confidence: 99%